Assessment of Risk Factors in Synanthropic and Wild Rodents Infected by Pathogenic Leptospira spp. Captured in Southern Chile - Jhuliana Luna; Miguel Salgado; Carlos Tejeda; Manuel Moroni; Gustavo Monti (Animals, 2020)
Leptospirosis is caused by pathogenic Leptospira, and synanthropic and wildlife species of rodents are an important source of infection; however, much of the information about infection progression was obtained from murine models. The aim of this study was to assess infection status and risk factors associated with pathogenic Leptospira in synanthropic and wild rodent species and describe histopathological lesions in several organs from naturally infected animals. In a cross-sectional study, 121 rodents from three synanthropic species and two wild species were trapped in dairy farms in Southern Chile. Liver, heart, kidney, and lungs from trapped animals were fixed in formalin and stained with hematoxylin–eosin. Tissues with lesions consistent with Leptospira infection were tested by immunohistochemistry (IHC) and real-time polymerase chain reaction (qPCR) using the LipL32 antigen. Risk factors were assessed by a conditional mixed-logistic regression model. More than half (56.7%) of the negative reactors to the microscopic agglutination test were identified as infected either by IHC/qPCR. A lower risk of infection compared to the rest of the seasons was found in the fall, and the synanthropic species have a lower risk of infection in comparison with the wildlife species. IHC and qPCR contributed to the identification of pathogenic Leptospira in related histological lesions and 50% more infections than serology.